Trust and trustworthiness under the prospect theory: A field experiment in Vietnam - Quang Nguyen; Marie-Claire Villeval; Hui Xu (Institute for the Study of Labor (IZA), 2012)
We study the influence of risk and time preferences on trust and trustworthiness by conducting a field experiment in Vietnamese villages and by estimating the parameters of the Cumulative Prospect Theory and of quasi-hyperbolic time preferences. We find that while probability sensitivity or risk aversion do not affect trust, loss aversion influences trust indirectly by lowering the expectations of return. Also, more risk averse and less present biased participants are found to be trustworthier. The experience of receiving remittances influences behavior and a longer exposure to a collectivist economy tend to reduce trust and trustworthiness.
Keywords: C91; C93; D81; D90; O10; O53; 330; trust; trustworthiness; risk preferences; time preferences; Cumulative Prospect Theory; Vietnam; field experiment; Vertrauen; Prospect Theory; Risikopräferenz; Zeitpräferenz; Feldforschung; Vietnam